Quill the forest keeper - Tolman, Marije; Colmer, David, 1960- (Montclair [New Jersey] : Levine Querido, 2024)
'Long, long ago it was so busy. Nobody had time to stop for a moment. Everything and everyone had to be higher, faster, further, bigger, prettier, more!' Thus begins Grandpa Hedgehog's story of the Rush Era. A time not so different from our own, where everyone was constantly on the move and no one had time to stop for a moment, even to care for the forest. Everyone except for Quill.
Translation of: Egalus.
K-3
Keywords: Hedgehogs -- Juvenile fiction; Grandfathers -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Ecology -- Juvenile fiction; Communities -- Juvenile fiction; Values -- Juvenile fiction; Hedgehogs -- Fiction; Animals -- Fiction; Grandfathers -- Fiction; Forests and forestry -- Fiction; Ecology -- Fiction; Communities -- Fiction; Values -- Fiction; Animal fiction